1998
DOI: 10.1002/(sici)1097-0320(19980901)33:1<83::aid-cyto10>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of binding of HIV-1 anti-p24 antibodies to CD4+ lymphocytes from HIV-infected subjects

Abstract: The clinical utility of a flow cytometric assay (FCA) for intracellular HIV p24 antigen was evaluated in a group of HIV‐1‐infected subjects. A previously described method, p24‐FCA (1), was modified to minimize nonspecific staining and to include irrelevant isotype‐matched control antibodies. Blood mononuclear cells from 32 HIV‐1 seropositive subjects and 14 HIV‐1 seronegative controls were examined. In HIV‐1 seropositive individuals, the proportion of CD4+ lymphocytes that bound the p24 monoclonal and the isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The detection of p24+ cells by flow cytometry in clinical samples is technically challenging, since antibodies specific for HIV proteins are notorious for their limited specificity [4345]. We hypothesized that combining antibodies targeting several viral epitopes would reduce the number of false positive events by improving the specificity of the staining.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of p24+ cells by flow cytometry in clinical samples is technically challenging, since antibodies specific for HIV proteins are notorious for their limited specificity [4345]. We hypothesized that combining antibodies targeting several viral epitopes would reduce the number of false positive events by improving the specificity of the staining.…”
Section: Resultsmentioning
confidence: 99%
“…Flow-cytometric approaches detecting viral proteins would allow to directly phenotype HIV-infected cells. Studies reporting detection of p24+ cells by flow cytometry in clinical samples [41, 42] may not exclusively capture HIV-infected cells due to the low specificity of antibodies targeting p24 [4345]. Consistent with these findings, Graf et al showed that cells expressing high levels of p24+ are highly enriched for HIV DNA, whereas cells expressing intermediate or low levels of p24 are more rarely infected [41].…”
Section: Introductionmentioning
confidence: 96%
“…These advances have resulted from the optimization of fixation and permeabilization protocols, along with the ongoing development of directly conjugated monoclonal (mAb) and polyclonal antibodies to many proteins, including viral antigens (14–16). These improvements have allowed for increased signal‐to‐noise ratios and alleviation of problems encountered in earlier studies, such as background staining due to nonspecific binding of polyclonal antibodies or secondary antibodies and lack of sensitivity (17–19). Flow cytometric methods for the intracellular detection of the HIV‐1 p24 core antigen in patient peripheral blood mononuclear cells (PBMC) were developed initially as a potential marker for monitoring disease progression and the efficacy of antiviral therapies.…”
mentioning
confidence: 99%
“…Flow cytometric methods for the intracellular detection of the HIV‐1 p24 core antigen in patient peripheral blood mononuclear cells (PBMC) were developed initially as a potential marker for monitoring disease progression and the efficacy of antiviral therapies. Whereas some studies reported that HIV‐1 p24 antigen‐positive cells increased in patients with advanced disease (6, 9, 20, 21), others have suggested that flow cytometry p24 assays may overestimate the number of PBMC infected with HIV due to nonspecific binding of p24 antibodies (18, 19, 22). The sensitivity and specificity of this assay remain controversial for detecting infected PBMC from HIV‐1–infected patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation